The US credit crunch of 2007: A Minsky moment - Charles J. Whalen (Levy Economics Institute of Bard College, 2007)
It is now clear that most economists underestimated the widening economic impact of the credit crunch that has shaken American financial markets since at least mid-July. A credit crunch is an economic condition in which loans and investment capital are difficult to obtain; in such a period, banks and other lenders become wary of issuing loans, so the price of borrowing rises, often to the point where deals simply do not get done. Financial economist Hyman P. Minsky (1919-1996) was the foremost expert on such crunches, and his ideas remain relevant to understanding the current situation. This brief by Charles J. Whalen demonstrates that the US credit crunch of 2007 can aptly be described as a Minsky moment. It begins by taking a look at aspects of this crunch, then examines the notion of a Minsky moment, along with the main ideas informing Minsky's perspective on economic instability. At the heart of that viewpoint is what Minsky called the financial instability hypothesis, which derives from an interpretation of John Maynard Keynes's work and underscores the value of an evolutionary and institutionally grounded alternative to conventional economics. The brief then returns to the 2007 credit crunch and identifies some of the key elements relevant to fleshing out a Minsky-oriented account of that event.
Keywords: 330; Kreditmarkt; Bankenkrise; USA